Analysis of Primary/Containment Coupling Phenomena Characterizing the MASLWR Design During a SBLOCA Scenario - Mascari, Fulvio; Vella, Giuseppe; Woods, Brian G.; Welter, Kent; D'Auria, Francesco (IntechOpen, 2012)
None